2019
DOI: 10.1186/s12967-019-2008-y
|View full text |Cite|
|
Sign up to set email alerts
|

Serum CCL20 combined with IL-17A as early diagnostic and prognostic biomarkers for human colorectal cancer

Abstract: Background Noninvasive and effective methods of early diagnosis of colorectal cancer (CRC) are underexplored. Inflammation is known to play an important role in the tumor microenvironment of CRC. Therefore, the aim of this study was to elucidate novel inflammatory biomarkers related to early diagnosis and prognosis of CRC. Methods Based on the results from a multiplex assay and a pan-cancer screening of TCGA data with 18 cancer types, we identified several targeted biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…This chemokine has a number of functions potentially relevant to bovine reproduction including in the coordination of signals between the ovary and the uterus as well as the chemotactic response to sperm 36 . Circulating levels in serum are attracting recent interest in human studies 37 , and its significantly elevation in response to post partum disease warrants further investigation. Interestingly however, the vast majority of DEG in this comparison were decreased in cows which subsequently developed PVD relative to cows which remained healthy.…”
Section: Discussionmentioning
confidence: 99%
“…This chemokine has a number of functions potentially relevant to bovine reproduction including in the coordination of signals between the ovary and the uterus as well as the chemotactic response to sperm 36 . Circulating levels in serum are attracting recent interest in human studies 37 , and its significantly elevation in response to post partum disease warrants further investigation. Interestingly however, the vast majority of DEG in this comparison were decreased in cows which subsequently developed PVD relative to cows which remained healthy.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis of CRC, which is common among both men and women [ 60 ], is important for improving prognosis, with CCL20 being a candidate biomarker. Accordingly, studies have shown that patients with CRC have significantly higher serum CCL20 and interkeukin-17 A (IL17A) levels than healthy individuals, and that receiver operating characteristic curve analysis combining CCL20 and IL17A is effective in distinguishing patients with CRC from healthy individuals [ 42 ]. Recurrence and metastasis in CRC have been the main causes of death among patients, while chemoresistance has remained a major therapeutic challenge.…”
Section: Role Of the Ccl20-ccr6 Axis In Cancer Progression And Tummentioning
confidence: 99%
“…26 In addition, the gene polymorphism of IL12A was correlated with the risk and prognosis of various tumors, including lung cancer, 27 HCC, 28 cervical cancer, 29 and gastric cancer. 30 As a chemokine, CCL20 plays an important role in the progression of tumors and is closely related to the prognosis of patients with solid tumors such as colon cancer, 31 lung cancer, 32 and pancreatic cancer. 33 PRELI was originally thought to be expressed on germinal center B lymphocytes.…”
Section: Discussionmentioning
confidence: 99%